A geographic information system (GIS) approach for storing and managing geotechnical properties at Bandar Seri Manjung, District of Manjung, Perak Darul Ridzuan / Wan Nur Syazwani W. M, Rusamah Abdul Jalil and Noorsazwan Ahmad Pugi - W. M, Wan Nur Syazwani; Abdul Jalil, Rusamah; Ahmad Pugi, Noorsazwan (2012)
This paper explains the development of Geographic Information System (GIS) in geotechnical properties. GIS is used in store geotechnical properties such as soil types, soil depth or layer and water level at Bandar Seri Manjung, District of Manjung, Perak Darul Ridzuan. With help GIS technology, geotechnical properties are store in the form of softcopy and people can make quick decision especially during preliminaries construction stage. Spatial analysis is used in the process of modeling, examining, and interpreting the model results. Attribute data information, geographic referenced data are the important item in spatial analysis. The chapter concludes with some discussion of the future prospect about GIS in geotechnical aspect